An experimental study on the mechanical and durability properties assessment of E-waste concrete - Ullah, Z. (Elsevier Ltd, 2021)
Electronic waste (E-waste) is increasing constantly around the globe, affecting human health and the environment adversely. To cope with the alarming situation of E-waste production, it is essential to find its potential applications and limit its adverse environmental impacts. This study aims to examine the influence of E-waste as a partial replacement of natural coarse aggregates (NCA) on both the fresh and hardened concrete properties. Four types of concrete mix with manufactured plastic aggregate as a partial substitute for NCA prepared with substitution levels up to 20 (by weight of NCA). The mechanical performance of E-waste concrete was assessed based on the compressive and splitting tensile strength test results and the durability characteristics were evaluated via thermal exposure, sorptivity coefficient, ultrasonic pulse velocity (UPV), abrasion resistance, and alternate wetting and drying. The results revealed that the compressive and tensile strengths of E-waste concrete reduced in the range of 6.3â17.1 and 23.5â32.4, respectively for replacement ratios of 10â20. However, the workability and durability properties improved with the E-waste aggregate incorporation. A substantial reduction in the sorptivity coefficient, UPV value, and abrasion loss was observed with an increasing amount of E-waste aggregates. Furthermore, concrete with E-waste aggregates showed better performance against alternate wetting and drying cycles compared to normal concrete and the increasing percentage of E-waste had no substantial effect on the drop in the compressive strength of E-waste concrete against thermal exposure. Â© 2021 Elsevier Ltd